European Rotorcraft Forum 2014 : conference programme & proceedings, 2-5 September 2014 Southampton, UK. (Royal Aeronautical Society, 2014)
The European Rotorcraft Forum (ERF) is one of the premier events in the rotorcraft community's calendar, bringing together manufacturers, research centres, academia, operators and regulatory agencies to discuss advances in research, development, design, manufacturing, testing and operation of rotorcraft. This Forum was the 40th in a series of meetings, which take place annually across Europe, rotating around the United Kingdom, Germany, France, Italy, the Netherlands and Russia. The first ERF was held in Southampton, England, in 1975, and the most recent in Moscow, Russia, in 2013. The 40th European Rotorcraft Forum was organised by the Royal Aeronautical Society. In celebration and commemoration of 40 successful years, the Forum returned to its birthplace in Southampton from the 2nd to the 5th of September, 2014.